Testing the feasibility of using the Edmonton Symptom Assessment System (ESAS) to assess caregiver symptom burden. Issue 1 (7th March 2017) - Tanco, Kimberson; Vidal, Marieberta; Arthur, Joseph; Delgado Guay, Marvin; Hui, David; Liu, Diane; Chisholm, Gary; Bruera, Eduardo
ABSTRACT: Objective: Caregiver symptom assessment is not part of regular clinical cancer care. The ESAS (Edmonton Symptom Assessment System) is a multidimensional tool regularly used to measure symptom burden in patients but not caregivers. The objectives of the present study were to determine the feasibility of the ESAS in caregiver completion (defined as ≥ 9 of 12 items) and determine its concurrent validity with the Zarit Burden Interview–12 (ZBI–12). Method: We conducted a prospective study on 90 patient–primary caregiver dyads seen in an outpatient supportive care center in a cancer center. The 12 item ESAS–FS (financial–spiritual) was completed by the dyads along with other clinical and psychosocial measures. Results: The caregiver ESAS was found to be feasible (90/90 caregivers, 100% completed ≥ 9/12 items) and useful (66/90 caregivers, 73%) by caregivers to report their symptom burden. Some 68 of 90 (76%) caregivers had symptom distress scores ≥ 4 on at least one symptom. A significant association was found between the ESAS scores of caregivers and patients for fatigue (0.03), depression (<0.01), anxiety (<0.01), sleep (0.05), well-being (<0.01), financial distress (<0.01), spiritual pain (<0.01), and total ESAS score (<0.01). Concurrent validity with the ZBI–12 was not achieved ( r = 0.53, p = 0.74). A significant correlation was found between caregiver ESAS scores and time spent feeding, housekeeping, total combined caregiver activities, and total ZBI–12 scores. Significance of results: The caregiver ESAS is a feasible tool and was found useful by our caregivers. Further research is needed to modify the ESAS based on caregivers' recommendations, and further psychometric studies need to be conducted.